2015
DOI: 10.1128/jvi.00454-15
|View full text |Cite
|
Sign up to set email alerts
|

Borna Disease Virus Phosphoprotein Modulates Epigenetic Signaling in Neurons To Control Viral Replication

Abstract: Understanding the modalities of interaction of neurotropic viruses with their target cells represents a major challenge that may improve our knowledge of many human neurological disorders for which viral origin is suspected. Borna disease virus (BDV) represents an ideal model to analyze the molecular mechanisms of viral persistence in neurons and its consequences for neuronal homeostasis. It is now established that BDV ensures its long-term maintenance in infected cells through a stable interaction of viral co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
1
17
0
3
Order By: Relevance
“…Treatment with SAHA can enhance memory formation in rats and mice [17], and improves memory deficits in animal models of neurodegenerative disorders [18,19]. Infection with a laboratory BoDV-1 strain affects site-specific histone acetylation in cortical [20] and hippocampal neurons [21]. Moreover, our previous study showed that infection with a human BoDV-1 strain epigenetically impacts the human oligodendroglial (OL) cell proteome through histone acetylation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with SAHA can enhance memory formation in rats and mice [17], and improves memory deficits in animal models of neurodegenerative disorders [18,19]. Infection with a laboratory BoDV-1 strain affects site-specific histone acetylation in cortical [20] and hippocampal neurons [21]. Moreover, our previous study showed that infection with a human BoDV-1 strain epigenetically impacts the human oligodendroglial (OL) cell proteome through histone acetylation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Cortical primary neurons were prepared from Sprague-Dawley rat embryos at gestational day 17 as described previously (72). If needed, they were transfected using the Amaxa rat neuron nucleofector kit (Lonza) following the manufacturer instructions (5.10 6 neurons with 3 µg of plasmid DNA, by using the G-13 program on nucleofector apparatus) by plasmids expressing Flag-MeCP2 isoforms, kind gift from Angus Wilson (73).…”
Section: Methodsmentioning
confidence: 99%
“…At the molecular level, BDV has the remarkable property for a RNA virus to replicate into the nucleus, in close association with cellular chromatin (122). Moreover, a recent study from our team demonstrated that BDV infection resulted in a decrease of H2B and H4 acetylation on selected lysine residues in primary cultures of cortical neurons (123) (Figure 3). We also showed that the viral phosphoprotein, a cofactor of the viral polymerase, was responsible for this decrease in histone acetylation, by inhibiting cellular HAT activity.…”
Section: Infectious Agentsmentioning
confidence: 98%